More than Just Insults: Rethinking Sociology's Contribution to Scholarship on Racial Microaggressions. Issue 2 (May 2017) - Embrick, David G.; Domínguez, Silvia; Karsak, Baran
Abstract : Our goal with this special issue is to expand currently untapped ideas about racial microaggressions from a sociological point of view. As noted, research on this issue comes largely out of psychiatry, psychology, and education—disciplines that tend to place less emphasis on structural and institutional causes of racism. There is a need for more sociologically guided research to examine how subtle, covert, and non‐apparent forms of racism affect minorities physiologically, psychologically, and emotionally—and how these micronooses can best be understood in a larger context of structural racism. Examination of racial microaggressions from a sociological point of view promises additional insight to help understand the complexities of contemporary race and racism in America and abroad.